EXTH-69. MAGNETIC HYPERTHERMIA THERAPY OF EXPERIMENTAL GLIOBLASTOMA IN COMBINATION WITH CHEMORADIATION. (5th November 2018) - Bouras, Alexandros; Mahmoudi, Keon; Bozec, Dominique; Gerald, Joe; Raj, Jesu; Ivkov, Robert; Hadjipanayis, Constantinos
Abstract: INTRODUCTION: Fractionated radiation therapy (RT) combined with chemotherapy (temozolomide; TMZ), known as chemoradiation (CRT), has provided the greatest benefit to glioblastoma (GBM) patients. Magnetic hyperthermia therapy (MHT) consists of intratumoral heat generation after deposition of magnetic iron-oxide nanoparticles (MIONPs) that are subjected to an external alternating magnetic field (AMF). MHT may potentiate the cytotoxic effects of CRT on tumor cells. We have developed MIONPs that demonstrate heating efficacy for MHT. METHODS: Intracranial heating efficacy and toxicity studies were performed in healthy mice using MIONPs solutions with a clinically relevant AMF treatment (450kHz, 200G) after convection-enhanced delivery (CED). Bioluminescence imaging (BLI) was used to assess the in vivo efficacy of intracranial MHT in combination with fractionated RT in a mouse syngeneic GBM model. A pilot survival study of athymic nude mice with invasive, therapy-resistant orthotopic human GBM intracranial xenografts was completed after combination treatment with MHT and CRT. Quantification of TMZ levels in intracranial xenografts and surrounding brain tissue after MHT was performed using liquid chromatography–mass spectrometry (LC-MS). RESULTS: A concentration-dependent temperature increase by the MIONPs after CED and an AMF was observed rapidly in the brain. No temperature elevation was observed in either the contralateral brain hemisphere or the rectum, supporting the localized intracranial heating effect. No severe acute and long-term side effects were observed after MIONP CED. A marked decrease in tumor size was found with MHT and RT by BLI. Significantly prolonged animal survival occurred with MHT and CRT in comparison to monotherapy. Increased TMZ levels were measured in xenografts and surrounding brain tissue after MHT and TMZ treatment. CONCLUSIONS: We have confirmed the safety and feasibility of intracranial MHT in a rodent glioma model. Furthermore, we have demonstrated the chemoradiosensitivity enhancement of therapy-resistant human GBM xenografts after MHT.